(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
A field experiment was carried out to evaluate the effect of leaf extracts of Sida acuta Burm. f. and Chromolaena odorata L. in controlling insect pests of Celosia argentea L. and Amaranthus cruentus L. The experiment was laid out in randomized complete block design and the treatments were replicated three times. Extracts obtained from the plants at 240 g/L of ethanol were applied as botanical insecticides. These extracts were examined along with a synthetic insecticide (Cypermethrin) including untreated control. Data were collected on number of Cletus spp. and Hymenia recurvalis per plant. Result shows that C. argentea sole treated with S. acuta and C. odorata was not infested by Cletus spp., and significantly (p<0.05) different from A. cruentus and C. argentea intercrop treated with S. acuta and C. odorata at 2 weeks after treatment. C. argentea treated with S. acuta had the least number of H. recurvalis (1.00) which was not significantly (p>0.05) different from Cypermethrin in both sole and intercrop at 4 WAT. A. cruentus and C. argentea planted sole or in intercrop treated with botanical and synthetic insecticides had lower numbers of H. curvalis which were significantly different from untreated control at 8 and 10 WAT. This study showed that S. acuta performed better than C. odorata against the target insect pests and therefore recommended for incorporation into Integrated Pest Management irrespective of whether sole or intercropping was adopted